Evaluasi Pembelajaran Biologi pada Materi Sistem Imun dengan Model Discovery Learning dalam Pengembangan Kognitif Belajar Siswa Kelas XI MAS PAB 1 SAMPALI - Hernita, Friska (Undiksha, 2023)
Evaluation is a process where a teacher can measure the cognitive value of students in doing something in learning. In otherwords, the measurement of training is something that must be owned by an educator in carrying out responsibilities such aseducators, because it relates to the bureau and the responsibilities of an educator in learning, namely learning is included incarrying out the end of learning. The purpose of the mini set is to evaluate biology lessons in the Immune System subject usingDiscovery Leaning in the cognitive development of high school students in class XI MAS PAB 1 SAMPALI Medan. The methodused in this research is the quantitative method. The instrument used in the form of a written test to test students' understandingof the material taught using LKS (Student Worksheet). The research location is at JL. HITA MARKET NO. 69 SAMPALI withclass XI samples. The research was conducted on 27 May 2022 at 8.45-10.00. Based on the results of the study, it was foundthat the immune system material using the Discovery Learning model can solve problems on its own related to the materialand can answer questions, because the questions given are related to life and students' critical thinking skills on the immunesystem material.